User acceptance of Academic Information System Management (AIMS) using UTAUT model / Nik Noor Nadiah Md Ibrahim - Md Ibrahim, Nik Noor Nadiah (2016)
Acceptance of Academic Information Management System (AIMS) is raised as a concern in many organizations, especially in educational institutions. AIMS in UiTM which is currently functional for two modules, Curriculum Management System and Examination Management System are used by the academic staffs who are designated as resource persons. The organization has encountered problems and challenges in ensuring user acceptance with the usage of the system. Besides, there is no one study conducted to evaluate the user acceptance of AIMS in UiTM. In regards the issue, a study is conducted to study the user acceptance of AIMS by using Unified Theory of Acceptance and Use of Technology (UTAUT) Model. User acceptance of AIMS is discussed in depth as to measure how the system is considered significant and effective for use of academic staffs in UiTM by studying the relationship between Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Condition and Actual Usage of AIMS system. The study proposed a modified UTAUT model where Behavioural Intention is excluded from the framework. Significance of relationship between independent variables and user acceptance of AIMS are determined by the data analysis done in SPSS tool. Findings of the study show that Performance Expectancy, Effort Expectancy and Facilitating Condition have positive effects on Actual Usage of AIMS where correlation results are true at 0.852, 0.757 and 0.315 where significance level, p < 0.1. However, Social Influence shows no positive effects on Actual Usage of AIMS where correlation reading shows -0.130 at significance level,p < 0.1. Meanwhile, moderating factors, age, gender and work experience are included to study the influence of Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Condition on Actual Usage of AIMS. Moderating factors, gender and age are found not to moderate the influence of Performance Expectancy on Actual Usage of AIMS. These moderating factors and work experience are not significant to moderate the influence the Social Influence on Actual Usage of AIMS. In contrast, the influence of Effort Expectancy on Actual Usage of AIMS is moderated by gender, age and work experience. On the same finding, the influence of Facilitating Condition on the Actual Usage of AIMS is moderated by age and work experience. Based on the findings in relationship studies on Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Condition on Actual Usage of AIMS, a multiple regression analysis is conducted to study the acceptance of AIMS. With R square of 0.729, the system is concluded to be accepted and used by the organization.